Model Kesetaraan Gender Di Arena Politik (Studi Penguatan Posisi Perempuan Dalam Politik di Kabupaten Aceh Utara) - Cut Sukmawati; Murniati Murniati; Ferizaldi Ferizaldi (Puslatbang KHAN, 2014)
This paper is aiming at explorer the phenomenon of political representation of women in the 2014 legislative elections in Aceh. In the tradition of patriarchal culture,